Deterministic and Etching‐Free Transfer of Large‐Scale 2D Layered Materials for Constructing Interlayer Coupled van der Waals Heterostructures. Issue 5 (16th February 2018) - Tao, Li; Li, Hao; Gao, Yun; Chen, Zefeng; Wang, Lei; Deng, Ya; Zhang, Jian; Xu, Jian‐Bin
Abstract: Transfer of large‐scale 2D atomic layers onto desired targets is crucial for the integration toward practical applications. Conventional wet etching transfer of 2D materials grown on insulating substrates suffers from the degraded film quality caused by the prolonged exposure of harsh chemicals. Also, both the detaching from initial substrate and the attaching to target processes are not spatially deterministic. Herein, by adopting the water‐soluble polyvinyl alcohol as a viscoelastic mediator and polymethyl‐methacrylate as a protecting layer, a green and robust transfer technique is developed for various grown 2D materials. This method is of high degree of freedom, which can realize both selective peel‐off and aligned release. The transferred materials maintain their pristine qualities, as probed by various spectroscopic/microscopic characterizations. This technique promises a universal applicability for a diverse range of 2D materials and growth/target substrates, facilitating facile fabrication of 2D electronic devices with improved performance. Furthermore, by performing restacking steps, van der Waals heterostructures can be built. As a proof of concept, the artificial assembly of monolayer MoS2 /WSe2 heterostructure is fabricated, and the strong interlayer coupling from photoluminescence quenching and emerging Raman modes at the junction areas is found, indicating that the method guarantees the ideal interfaces between the transferred materials. Abstract : Universal transfer technique that contains selective peel‐off and aligned stacking is demonstrated for chemical vapor deposition grown 2D materials on insulating substrates. The intrinsic optical and electrical properties of the 2D materials are highly preserved during the transfer. The stacked monolayer MoS2 /WSe2 heterostructures present strong interlayer coupling, evidenced by the large photoluminescence quenching and the emerging Raman modes at the junction.